Descriptions of two new species of Myrmedonota Cameron (Staphylinidae: Aleocharinae) from Mexico with comments on the genus taxonomy and behavior - Mathis, Kaitlyn A.; Eldredge, K. Taro (Zootaxa, 2014)
Two new species of Myrmedonota, M. shimmerale n. sp. and M. xipe n. sp., are described, and the genus is recorded from Mexico for the first time. Dorsal habitus photographs, illustrations of the median lobe and spermatheca are presented for diagnostic purposes. We suggest that Myrmedonota is in fact diverse in the New World and that its taxonomy is already in a state of confusion. New behavioral observations show that: (1) Myrmedonota species will aggregate towards agitated ants, possibly to prey on them; (2) Myrmedonota will form mating swarms, either with no apparent landmark or in the vicinity of ants.